2013
DOI: 10.1177/0748730413493862
|View full text |Cite
|
Sign up to set email alerts
|

Dim Light at Night Disrupts Molecular Circadian Rhythms and Increases Body Weight

Abstract: With the exception of high latitudes, life has evolved under bright days and dark nights. Most organisms have developed endogenously driven circadian rhythms which are synchronized to this daily light/dark cycle. In recent years, humans have shifted away from the naturally occurring solar light cycle in favor of artificial and sometimes irregular light schedules produced by electrical lighting. Exposure to unnatural light cycles is increasingly associated with obesity and metabolic syndrome; however the means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
190
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 47 publications
10
190
3
2
Order By: Relevance
“…Interestingly, the amplitude of electrical activity in the SCN is linked to sympathetic outflow toward multiple organs (25). This mechanism also explains previous findings that exposure of mice to dim light (5 lx) during 10-h nights for 4 wk already results in an increase in body weight, which was accompanied by an attenuated amplitude of circadian gene expression in the hypothalamus (26). Additionally, sympathetic outflow toward BAT depots other than interscapular BAT = not significant, *P < 0.05, **P < 0.01, ***P < 0.001.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, the amplitude of electrical activity in the SCN is linked to sympathetic outflow toward multiple organs (25). This mechanism also explains previous findings that exposure of mice to dim light (5 lx) during 10-h nights for 4 wk already results in an increase in body weight, which was accompanied by an attenuated amplitude of circadian gene expression in the hypothalamus (26). Additionally, sympathetic outflow toward BAT depots other than interscapular BAT = not significant, *P < 0.05, **P < 0.01, ***P < 0.001.…”
Section: Discussionsupporting
confidence: 72%
“…For instance, as the expression of the negative clock gene Per is normally low at night, light administered during the subjective night should significantly alter the pattern of Per expression and consequently affect other components of the circadian clock. Dim light at night (~5 lux) has been shown to alter circadian clock gene expression of mice (Fonken et al 2013a ; Fonken andNelson 2014 ) and Siberian hamsters (Bedrosian et al 2013 ), including Bmal1, Per1, Per2, Cry1, Cry2, and Rev Erb. These effects have been reported in both the SCN and the liver, with the latter associated with increased body weight independently of daily caloric intake (Fonken et al 2013a ).…”
Section: Future Directionsmentioning
confidence: 99%
“…MLT treatment consistently reduced adiposity and body mass in several rodent species [182]. Several studies have demonstrated that chronic exposure to dim light at night increases body mas gain in mice, and this effect is suggested to be mediated by the ALAN-induced MLT suppression [91,92,191,192]. Finally, MLT has been reported to influence several metabolic factors, such as insulin, insulin-like growth factor, growth hormone, glucose metabolism, and others, which could directly control body mass homeostasis [193].…”
Section: Alan Obesity and Cancerthe Epigenetic Nexus To Melatoninmentioning
confidence: 97%
“…ALAN treatments result in a significant reduction in daily energy expenditure and body mass of social voles (Microtus socialis) and laboratory rats [89,90]. In another mice experiment, circadian disruption by dim florescent ALAN has been reported to change feeding behavior and increased mass gain [91,92]. This contrasting effect of ALAN on body mass could be at least partially explained by the different light intensity levels used in the comparative studies; where the direction of body mass change can be directly related to light intensity levels.…”
Section: Lan and Circadian Disruption Of Metabolic Responsesmentioning
confidence: 98%